Physico-chemical Characteristics of some Typical Soils of Indian Forests - Yadav, J. S. P. (Indian Forester, 1968)
The paper describes the results of eleven typical soils under certain important types of forests found in India. In general, the soils of drier areas have higher pH values and are poorer in organic matter and nitrogen, but possess greater quantities. of bases like calcium than the soils of more humid areas. Low level of organic matter and nitrogen, deficiency of moisture, poor structure, calcareousness, alkaline reaction, presence of kankar pan, excessive salt content, etc., are some of the factors which lead to the growth of only xerophytic species in some drier localities. Coastal sand under littoral vegetation is associated with poor nutrient status. The highest amount of organic matter and nitrogen is found in the soil under high level conifers. The ferruginous soil with good supply of manganese appears to be favourable for natural regeneration of sal (Shorea robusta) in Bihar. Teak (Tectona grandis) attains better quality on moist soil developed from basalt which is acidic and has adequate amount of exchangeable calcium and satisfactory P-availability. These data show that the soils under different forest vegetation differ considerably in their physical and chemical characteristics and suggest the need for more systematic detailed studies to have a thorough appraisal of the relationship between soil and vegetation and to develop most appropriate methods of management.